The Relationship between Internet Addiction and Insomnia in Student Class IX - La Rakhmat Wabula; M. Taufan Umasugi; Wa Ode Nurlina; Angga Miftakhul Nizar; Restiyana Agus (Universitas Airlangga, 2020)
Introduction: Internet addiction can cause unfulfilled hours of sleep, which if left unchecked will lead to disruption of sleep patterns often called insomnia. The purpose of the research was to determine the relationship between internet addiction and insomnia.Methods: The design of the research was descriptive-analytic with a cross-sectional approach. The population in the research consisted of as many as 217 respondents with a sample size of 141 respondents. The variables used in the research were insomnia as the dependent variable and internet addiction as the independent one. The instrument used was a questionnaire with a univariate and bivariate analysis.Results: The results of the study used the Spearman Rho test with a value of p = 0,000.Conclusion: From these results, it could be concluded that there is a relationship between internet addiction and the incidence of insomnia. Internet addiction can cause unfulfilled hours of sleep, which if left unchecked will lead to disturbed sleep patterns often called insomnia. The research suggests that students pay more attention to their health by limiting or reducing the use of the internet for unimportant issues as it can reduce learning productivity and academic value and cause insomnia.